Taxation : a Fieldwork Research Handbook. - Oats, Lynne (Taylor & Francis, 2012)
Taxation is a subject of enquiry that cuts across a range of disciplines, including law, economics, politics, psychology, history and accountancy, to name a few. However, research into taxation as a social and institutional phenomenon -- rather than as abstraction from the real world -- is largely neglected. Taxation: A Fieldwork Research Handbook opens up new avenues of enquiry in the research of taxation by offering suggestions on how research might be conducted into actual tax practice, rather than abstract models. This book: Introduces tax as a field of enormous potential for research to a.